2022
DOI: 10.1177/00220426221109948
|View full text |Cite
|
Sign up to set email alerts
|

Medication-Assisted Treatment in Problem-solving Courts: A National Survey of State and Local Court Coordinators

Abstract: Problem-solving courts (PSCs) are a critical part of a societal effort to mitigate the opioid epidemic's devastating consequences. This paper reports on a national survey of PSCs (N = 42 state-wide court coordinators; N = 849 local court coordinators) and examines the structural factors that could explain the likelihood of a local PSC authorizing medication-assisted treatment (MAT) and MAT utilization. Results of the analyses indicate that MAT availability at the county level was a significant predictor of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Due to the timing of these questions, only a limited number of participants accessed the version of the survey with COVID-19 questions for the last five months of data collection. For this research note, we will only analyze data from the responses to the PSC coordinator survey that included the COVID-19 questions to examine shifting operations of local courts due to COVID-19; Faragó and colleagues (2022) report on the overall study findings. A convenience sample of 82 local courts located in 10 states answered specific questions about their COVID-19 operations.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the timing of these questions, only a limited number of participants accessed the version of the survey with COVID-19 questions for the last five months of data collection. For this research note, we will only analyze data from the responses to the PSC coordinator survey that included the COVID-19 questions to examine shifting operations of local courts due to COVID-19; Faragó and colleagues (2022) report on the overall study findings. A convenience sample of 82 local courts located in 10 states answered specific questions about their COVID-19 operations.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a recent study surveyed state prisons in states with disproportionate opioid overdose mortality and found that while all prison systems within the states surveyed reported offering at least one medication to treat OUD, only 7% of the 538 individual prisons within the states offered all three medication types (methadone, buprenorphine and naltrexone); 61% of the 538 prisons did not offer any type of MOUD [72]. A recent study on medications used in a nationally representative same of 832 problem solving courts reported that while 86% of the courts would authorize the use of medications, only 14% of those with an opioid use disorder were on MOUD [20]. Other models employing evidence-based cognitivebehavioral treatment (CBT are in place, including in the Federal Bureau of Prisons' non-residential treatment program (a 12-week course for those serving short sentences and/or who are transitioning back to the community as part of their SUD treatment, Federal Bureau of Prisons, n.d.).…”
Section: Limitations Of Political and Policymaking Leadership: Implic...mentioning
confidence: 99%